Hubungan Masa Kerja dengan Kadar 8-OHdG Urin pada Pekerja Pabrik Pengolahan Tembakau di Kabupaten Jember - Ardhia Putri Pratama (Fakultas Kedokteran, 2025)
Background: The length of the working period can increase the risk of accumulated damage due to exposure to harmful substances in the workplace. The processing of tobacco leaves produces tobacco dust containing various hazardous substances. Nicotine is the main component in tobacco dust released during tobacco processing. Chronic exposure to nicotine can lead to the accumulation of oxidative stress in the body which ultimately leads to DNA damage and increase the risk of disease. DNA damage can be measured through the biomarker 8-hydroxy-2'- deoxyguanosine (8-OHdG). Objective: This study aims to determine the relationship between working period and urinary 8-OHdG levels in tobacco processing factory workers in Jember Regency. Method: This study use an observational analytical method with a cross-sectional research design that was carried out from April to November 2024. Sampling was carried out by non-probability sampling technique with the purposive sampling method. The subject of this study is a tobacco processing factory worker at the PTPN X Ajong Gayasan Factory, Jember who comply the inclusion and exclusion criteria. Urine sample were taken to check 8-OHdG levels with ELISA method. Data analysis was carried out using the Spearman Rank test and Kruskal-Wallis test. Result: The average urinary 8-OHdG levels in this study were 228.52 ± 78.62 ng/mg creatinine, with a range between 84.4–413.6 ng/mg creatinine. Based on the working period categories, the average 8-OHdG levels in the working period of <6 years, 6–15 years, 16–25 years, and >25 years were 189.61, 240.25, 225.94, and 269.46 ng/mg creatinine, respectively. Spearman's test showed that the relationship between the working period and 8-OHdG levels was not statistically significant (p = 0.096, p>0,05; r = 0.254) and the correlation coefficient showed a weak positive relationship. Kruskal-Wallis test showed that there was no statistically significant difference between 8-OHdG levels with different working period groups (p = 0.096, p>0.05). Conclusion: There was no relationship between working period and urinary 8- OHdG levels in tobacco processing factory workers in Jember Regency.
Entry oleh Arif 2026 Maret 27
Keywords: 8-OHdG; DNA damage; Working period; Tobacco processing factory worker; Occupational health